1998
DOI: 10.1063/1.869572
|View full text |Cite
|
Sign up to set email alerts
|

Hydroelastic instability threshold in a turbulent boundary layer over a compliant coating

Abstract: In this paper we are concerned with a linear problem of hydroelastic instability in a turbulent boundary layer over a compliant coating of a ribbon-like material. A dispersion relation for hydroelastic waves is written in terms of complex stiffness coefficients that characterize the deformation of the compliant surface and the turbulent flow response to the wavy surface flexure. A membrane-type approximation is proposed for the stiffness coefficient of solid coating at sufficiently low frequencies. In order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…Results of numerical studies indicating benefits from compliant walls in the area of transition delay were reported by Carpenter & Morris (1990) and by Davies & Carpenter (1997). The case of transition manipulation is interesting, because in that case there is quite an extensive body of theoretical material on this problem, which is described by the linear stability theory and the asymptotic theory of transitional flows over compliant walls or in compliant channels (see Gajjar & Sibanda 1996;Larose & Grotberg 1996;Lucey & Carpenter 1995;Reutov & Rybushkina 1998;Riley, Gad-el-Hak & Metcalfe 1988;Yeo, Khoo & Zhao 1999). In fact, linear stability theory can provide satisfactory explanations for the failure of many experimental attempts aimed at delaying the onset of transition over compliant walls.…”
Section: Introductionmentioning
confidence: 99%
“…Results of numerical studies indicating benefits from compliant walls in the area of transition delay were reported by Carpenter & Morris (1990) and by Davies & Carpenter (1997). The case of transition manipulation is interesting, because in that case there is quite an extensive body of theoretical material on this problem, which is described by the linear stability theory and the asymptotic theory of transitional flows over compliant walls or in compliant channels (see Gajjar & Sibanda 1996;Larose & Grotberg 1996;Lucey & Carpenter 1995;Reutov & Rybushkina 1998;Riley, Gad-el-Hak & Metcalfe 1988;Yeo, Khoo & Zhao 1999). In fact, linear stability theory can provide satisfactory explanations for the failure of many experimental attempts aimed at delaying the onset of transition over compliant walls.…”
Section: Introductionmentioning
confidence: 99%
“…The main term of expansion in the right part of (2) Y0 coincides with tile linear elasticity of the flow calculated in [7]; the coefficient Yl characterizes the nonlinear properties of the TBL resI)onse. According to [8] The deformation of the surface of the elastic coating under an external action may be characterized by the complex elasticity K0 = -/)/tb.…”
Section: Nonlinear Dispersion Equation For Small-amplitude Hydroelastmentioning
confidence: 99%
“…In tile quasi-linear approximation, the elasticity is a flmction of (ka) 2 and may be considered as a virtual el~tsticity [7]. For small ka, we obtain tim dimensionless ela.sticity of the flow…”
Section: Nonlinear Dispersion Equation For Small-amplitude Hydroelastmentioning
confidence: 99%
See 2 more Smart Citations